Thalassemia intermedia in HbH-CS disease with compound heterozygosity for beta-thalassemia: challenges in hemoglobin analysis and clinical diagnosis - Tan, J.; Kok, J.L.; Tan, K.L.; Wee, Y.C.; George, E. (2009)
Co-inheritance of alpha-thalassemia with homozygosity or compound heterozygosity for beta-thalassemia may ameliorate beta-thalassemia major. A wide range of clinical phenotypes is produced depending on the number of beta-thalassemia alleles (-alpha(alpha alpha--/alpha alpha, —/-alpha). The co-inheritance of beta-thalassemia with a-thalassemia with a single gene deletion (-alpha/alpha) is usually associated with thalassemia major. In contrast, the co-inheritance of beta-thalassemia with two alpha-genes deleted in cis or trans (--/alpha alpha or -alpha/-alpha) generally produces beta-thalassemia intermedia. In Southeast Asia, the most common defect responsible for alpha-thalassemia is the Southeast Asian (SEA) deletion of 20.5 kilobases. The presence of the SEA deletion with Hb Constant Spring (HbCS) produces HbH-CS disease. Co-inheritance of HbH-CS with compound heterozygosity for beta-thalassemia is very rare. This study presents a Malay patient with HbH-CS disorder and beta degrees/beta(+)-thalassemia. The SEA deletion was confirmed in the patient using a duplex-PCR. A Combine-Amplification Refractory Mutation System (C-ARMS) technique to simultaneously detect HbCS and Hb Quong Sze confirmed HbCS in the patient. Compound heterozygosity for CD41/42 and Poly A was confirmed using the ARMS. This is a unique case as the SEA a-gene deletion in cis (--(SEA)/alpha) is generally not present in the Malays, who more commonly posses the two a-gene deletion in trans In addition, the beta-globin gene mutation at CD41/42 is a common mutation in the Chinese and not in the Malays. The presence of both the SEA deletion and CD41/42 in the mother of the patient suggests the possible introduction of these two defects into the family by marriage with a Chinese.